Bovine teeth as a novel matrix for the control of the food chain: liquid chromatography–tandem mass spectrometry detection of treatments with prednisolone, dexamethasone, estradiol, nandrolone and seven β2-agonists. Issue 1 (2nd January 2017) - Chiesa, Luca Maria; Nobile, Maria; Panseri, Sara; Biolatti, Bartolomeo; Cannizzo, Francesca Tiziana; Pavlovic, Radmila; Arioli, Francesco
ABSTRACT: Veterinary drugs usually have rapid clearance rates in the liver and kidney, hampering their detection in conventional matrices such as the liver or urine. Pharmacological principles such as esterification may be applied to facilitate the administration of veterinary drugs and increase drug half-life. Prednisolone, whose therapeutic administration is regulated for food producing animals in the EU, is available in its acetate form as well as nandrolone, a banned anabolic steroid, which may be obtained as nandrolone phenylpropionate and estradiol as a benzoyl ester. While the distribution and accumulation of lipophilic and hydrophilic substances in human teeth have been well documented, studies on residues in bovine teeth are lacking. We hypothesised that analysis of bovine teeth could be used to detect both regulated and banned veterinary drugs. Steroids may be illegally used as growth promoters in food producing animals, alone or combined with β2-agonists; therefore, we developed, and validated, in accordance with the Commission Decision 2002/657/EC, two analytical confirmatory LC-MS/MS methods to detect these classes of compounds following a unique liquid extraction procedure. Finally, we analysed teeth from three male Friesian veal calves treated with intramuscular estradiol benzoate, oral prednisolone acetate or intramuscular nandrolone phenylpropionate in combination with oral ractopamine, respectively, and from seven bovines from the food chain. Teeth from treated animals were positive for their respective drugs, with the exception of nandrolone phenylpropionate. One sample from a food chain bovine was positive for isoxsuprine, one of the seven β2-agonists studied. Non-esterified forms of the steroids were not found. These results demonstrate that bovine teeth are a suitable matrix for the determination of pseudoendogenous substances or illicit administration of veterinary drugs. GRAPHICAL ABSTRACT: